Pemberian Remisi Bagi Narapidana Tindak Pidana Korupsi Di Lembaga Pemasyarakatan Kelas IIA Binjai - Supian Natalis; Madiasa Ablisar; Mahmud Mulyadi; Syafruddin S. Hasibuan (Iuris Studia: Jurnal Kajian Hukum, 2021)
Corruption in Indonesia occurs systematically and spreads widely; it does not only injure the country financially but also violates the social and economic rights of the people. In order to eradicate corruption in Indonesia, the government has attempted to make various preventive and repressive strategies. The repressive strategy is aimed to give the sanction quickly and accurately imposed on those who have committed corruption. One of the attempts is the moratorium policy in giving remission to corrupt prisoners. However, Law No. 12/1995 on Penitentiary states that one of the prisoners’ rights is to obtain remission, including the rights of the corrupt prisoners.